(untitled) (Revista Internacional de Folkcomunicação, 2021)
In this article, we seek to narrate, record, and evaluate the procedures that characterize academic practices and the topics researched in a scientific community within the Research Group on Folkcommunication, Media and Interculturality of the 40th Brazilian Congress of Communication Sciences, held in 2017 by Intercom in Curitiba, capital of Paraná. It is a search for self-criticism, in the sense of observing how and to what extent the institution and development of procedures specific to the scientific environment institute and legitimize the scientific characterization of the GP in the midst of the Intercom congress, considering the insertion of Communication Sciences in the demands of the National Graduate System (SNPG) Research Group on Folkcommunication; Intercom 2017; Self-criticism; Communication Sciences.